Neonatal Isoflurane Does Not Affect Sleep Architecture and Minimally Alters Neuronal Beta Oscillations in Adolescent Rats - Manzella, Francesca M.; Gulvezan, Bethany F.; Maksimovic, Stefan; Useinovic, Nemanja; Raol, Yogendra H.; Joksimovic, Srdjan M.; Jevtovic-Todorovic, Vesna; Todorovic, Slobodan M. (Frontiers in Behavioral Neuroscience, 2021)
General anesthetics are neurotoxic to the developing rodent and primate brains leading to neurocognitive and socio-affective impairment later in life. In addition, sleep patterns are important predictors of cognitive outcomes. Yet, little is known about how anesthetics affect sleep-wake behaviors and their corresponding oscillations. Here we examine how neonatal general anesthesia affects sleep and wake behavior and associated neuronal oscillations. We exposed male and female rat pups to either six hours of continuous isoflurane or sham anesthesia (compressed air) at the peak of their brain development (postnatal day 7). One cohort of animals was used to examine neurotoxic insult two hours post-anesthesia exposure. At weaning age, a second cohort of rats was implanted with cortical electroencephalogram electrodes and allowed to recover. During adolescence, we measured sleep architecture (divided into wake, non-rapid eye movement and rapid eye movement sleep) and electroencephalogram power spectra over a 24 hour period. We found that exposure to neonatal isoflurane caused extensive neurotoxicity but did not disrupt sleep architecture in adolescent rats. However, these animals had a small but significant reduction in beta oscillations, specifically in the 12-20 Hz beta 1 range, associated with wake behavior. Furthermore, beta oscillations play a critical role in cortical development, cognitive processing, and homeostatic sleep drive. We speculate that dysregulation of beta oscillations may be implicated in cognitive and socio-affective outcomes associated with neonatal anesthesia.